Cooperation between Public Libraries and School Libraries and the Situation in Turkey - Bülent Yılmaz (Türk Kütüphaneciliği)
Each library type is a part of the national library system which aims to access the information for the society. Public and school libraries are two types of library which are close-set in this system. Cooperation between public and school libraries helps them to fulfil their functions. However, there are some pre-conditions and risks of the cooperation. Cooperation between public and school libraries in Turkey is quiet insufficient. Cooperation which will be realised in these conditions in Turkey won’t be able to contribute to solve their problems, meaningly.